A charged amino acid substitution within the transmembrane anchor of the Rous sarcoma virus envelope glycoprotein affects surface expression but not intracellular transport (The Rockefeller University Press, 1987)
Two point mutations were introduced by oligonucleotide-directed mutagenesis into the region of the Rous sarcoma virus envelope gene that encodes the hydrophobic transmembrane anchor of the receptor glycoprotein. Single-nucleotide substitutions ultimately converted a hydrophobic leucine, located centrally within the membrane-spanning domain, to either a similarly hydrophobic methionine or a positively charged arginine. The altered coding region was reinserted into an intact copy of the envelope gene, cloned into simian virus 40 late- replacement vector and expressed in primate cells. Analysis of envelope gene expression in CV-1 monkey cells revealed normal levels of synthesis of a membrane-spanning precursor for both the mutants; however, the arginine-containing mutant [mu 26(arg)] exhibited greatly reduced cell surface expression of mature protein, as determined by indirect immunofluorescence and 125I labeling of surface proteins. In experiments in which cells producing the mu 26(arg) polypeptide were pulsed with radioactive leucine and then chased for 5 h, no intracellular accumulation or extracellular secretion of mature products (gp85 and gp37) could be detected. Treatment of mu 26(arg)- infected cells with lysosomal enzyme inhibitors (chloroquine and leupeptin) resulted in the accumulation of gp85 and gp37, indicating that they were being degraded rapidly in lysosomes. The fact that terminally glycosylated and proteolytically cleaved env gene products were observed under these conditions showed that modifications associated with passage through the trans compartment of the Golgi apparatus occurred normally on the mutant polypeptide; thus insertion of a highly charged amino acid into the transmembrane hydrophobic region of gp37 results in the postGolgi transport to lysosomes. It is proposed that the insertion of this mutation into the transmembrane anchor of the envelope glycoprotein does not affect membrane association, orientation with respect to the membrane, or intracellular transport at early stages during maturation. At a step late in the transport pathway, however, the presence of the charged side chain alters the protein in such a manner that the molecules are transported to the lysosomes and degraded. It seems likely that transport of the protein from the trans-Golgi to the cell surface is either directly blocked, or that after expression on the cell surface the mature glycoprotein complex is unstable and rapidly endocytosed.